Processing and characterization of 〈001〉-textured Pb(Mg1/3Nb2/3)O3–Pb(Yb1/2Nb1/2)O3–PbTiO3 ceramics. Issue 13 (29th May 2017) - Duran, Cihangir; Cengiz, Salih; Ecebaş, Nazım; Dursun, Sinan; Akça, Erdem
Abstract: Abstract : 0.62[0.75(Pb(Mg1/3 Nb2/3 )O3 )–0.25(Pb(Yb1/2 Nb1/2 )O3 )]–0.38(PbTiO3 ) ceramics were successfully textured in [001] via the template grain growth method using 1–7 vol% platelike BaTiO3 (BT) templated (the Lotgering factor of 0.91 at 5 vol% BT). Dielectric spectra indicated a normal ferroelectric behavior without any frequency dispersion and no low-temperature phase transition. The chemically stable BT phase within the matrix gave rise to a composite effect and its relatively inferior properties affected the dielectric and electromechanical properties. The lower T C of the BT decreased the Curie temperature from 226 to 213 °C (with a depolarization temperature of 204 °C). Significantly higher levels of strain (0.33%), narrower hysteresis level (7.7%), higher piezoelectric strain coefficient (660 pm/V), and low-field (<5 kV/cm) piezoelectric strain coefficient (1340 pm/V) at 50 kV/cm were achieved at 5 vol% BT addition. These results are very promising for the fabrication of high performance transducer and actuator applications without severe temperature limitations.